Delivery of miRNA-126 through folic acid-targeted biocompatible polymeric nanoparticles for effective lung cancer therapy. (May 2022) - Golafzani, Forough N; Vaziri, Ali Z; Javanmardi, Masoud; Seyfan, Fatemeh; Yazdanifar, Mahboubeh; Khaleghi, Sepideh
Objective: Nanoparticle-based drug delivery systems (DDSs) have been playing a considerable role in the eradication of cancer. In this experimental study, we designed and synthesized folic acid (FA)-decorated chitosan (CS) nanocarrier for targeted delivery of miR-126 (as a therapeutic agent) to lung cancer A549 cells. Materials and methods: Therefore, the FA-CS-miR-126 nano-complex was perfectly developed and characterized by various analytical devices such as Fourier transform infrared (FT-IR) and dynamic light scattering (DLS) spectroscopies and as well as transmission electron microscopy (TEM). The size was determined lower than 100 nm for synthetics. Then, a gel retardation assay was performed to investigate the entrapment efficiency of nano-complex. Afterward, the sort of in vitro assays was implemented on A549 (FA receptor-positive lung cancer cell line) and MRC5 (normal human diploid cell line) to evaluate the therapeutic efficiency of FA-CS-miR-126. Results: As the cell viability (40.7 ± 2.98% cell viability after 72 h treatment with 500 nM), migration assay (weaker migration after 24 h and 48 h), apoptotic and autophagy genes expression level (Caspse9: sixfolds; BAX: 17 folds; ATG5: fourfolds; and BECLIN1: threefolds more than the control group), the reduced expression level of EGF-L7, as a target gene for miR-126 was evaluated by Real-Time PCR too, then, cell cycle arrest (8.66% of cells in sub-G1 phase), and cell apoptosis assay (21.0% of cancer cell in late apoptosis phase) were scrutinized. Conclusion: These results are remarkably approved the biocompatible and efficient performance of FA-CS-miR-126 as a promising DDS. Graphical Abstract